(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Bamboo leaves are one among the major agricultural by products and also a potential agro waste which are a rich source of silica. Bio-silica, SiO2 is the most abundant mineral on the earth’s crust and basically all photosynthetic plants contain a smaller proportion of it. Bamboo leaves were procured from a local farm and subjected to alkali extraction followed by acid treatment and further calcination to bring out pure nano-silica. The synthesized nano-silica particles were then characterized by UV, FT-IR, XRD, SEM-EDAX analysis and anti-microbial studies and was proven for commercial use. In order to prepare nano-silica polymer composites, there is an ardent need for a binder which was effectively prepared from castor oil which is a natural source of polyol and characterised by UV, FT-IR and H1, C13 NMR to prove its binding properties.